Prevalence of American Tegumentary Leishmaniasis in Brazil – a systematic review and meta-analysis (Revista Contexto & Saúde, 2023)
American tegumentary leishmaniasis (ATL) is a zoonotic disease that affects the skin and mucous membranes, and that is caused by different species of protozoa of the genus Leishmania. This disease has different clinical forms: cutaneous, disseminated cutaneous, diffuse and mucocutaneous leishmaniasis. The objective of this systematic review is to investigate the prevalence and distribution of ATL in Brazil. Studies that analised patients with ATL diagnosed by at least one of the parasitological gold standard methods, PCR, or by serological methods were included.  Thirteen studies from PubMed, Regional Portal of the Virtual Health Library (BVS), Brazilian Society of Dermatology, Virtual Health Library (IBECS), Literature in the Health Sciences in Latin America and the Caribbean (LILACS), Medical Literature Analysis and Retrieval System Online (Medline), Elsevier Embase, Cochrane Library, The National Institute for Health and Care Excellence (NICE), and Cumulative Index to Nursing and Allied Health Literature (CINAHL) were included. We found a combined prevalence in the general population of 40.0% (95% CI: 17.0–63.0%; weight 100%). When the prevalence was analyzed by state, we found a prevalence of 97.0% in Rio de Janeiro. The South and Southeast regions showed the highest percentage, with 48.0% followed by the Central-West region with 24.0%. The Montenegro’s intradermal reaction and cultures were the most used test to diagnose. This study revealed a high prevalence of ATL in several studies conducted in Brazil, a value that was influenced by the most studied regions such South and Southeast, where a prevalence of up to 48% was found.